Fusobacterium necrophorum causing infective endocarditis and liver and splenic abscesses - Marc Zac Handler; Benjamin Miriovsky; Howard E. Gendelman; Uriel Sandkovsky (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
A 25-year-old male without prior co-morbidities was admitted to hospital with Fusobacterium necrophorum bacteremia, where he was found to have liver and splenic abscesses. Further evaluation with echocardiography revealed a bicuspid aortic valve with severe insufficiency and a 1.68 x 0.86 cm vegetation. The patient required abscess drainage, intravenous antimicrobial therapy and aortic valve replacement. Complete resolution of the infection was achieved after valve replacement and a prolonged course of intravenous antimicrobial therapy. A brief analysis of the patient's clinical course and review of the literature is presented.